2019
DOI: 10.5455/medarh.2019.73.311-315
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Cytogenetic Findings and its Effect on the Outcome of Pediatric Acute Lymphoblastic Leukemia

Abstract: Introduction:Acute lymphoblastic leukemia (ALL) is one of the most common cancers in children and accounts for about ⅓ of cancers in children. The annual incidence of ALL is 4 patients per 100,000 children. Their peak age is between 2-5 Year. One of the most important prognostic factors is cytogenetic abnormalities which are very effective in determining treatment policy.Aim:To determine the frequency of cytogenetic findings and its effect on the outcome of children with ALL.Materials and Methods:This retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…In the present study, 57.9% (2182 patients) of the disease were observed in boys and the sex ratio of males to females was 1.37. These results are consistent with other studies; other studies showed higher incidence of disease in boys than in girls [4,9,[24][25][26]. According to the American Cancer Society's 2019 report, 55 percent of new cases and 56 percent of ALL deaths were boys [27].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, 57.9% (2182 patients) of the disease were observed in boys and the sex ratio of males to females was 1.37. These results are consistent with other studies; other studies showed higher incidence of disease in boys than in girls [4,9,[24][25][26]. According to the American Cancer Society's 2019 report, 55 percent of new cases and 56 percent of ALL deaths were boys [27].…”
Section: Discussionsupporting
confidence: 91%
“…26 Other studies have estimated the incidence rate of ALL to be between 3 and 7 per 100 000 children. 20,[27][28][29] In the present study, the mean and standard deviation of age were 5.90 ± 3.68 with a median age of 5 years. There was no statistically significant difference in age distribution between male and female children.…”
Section: Discussionmentioning
confidence: 82%
“…15,39 The highest incidence was observed between 2 and 5 years of age. In the studies by Hjalgrim et al, 40 Dohner et al, 41 Bahoush et al, 27 and Alrudainy et al, 42 the peak incidence of the disease was reported to be at the age of 2-5 years.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Leukemia ranks rst in incidence among pediatric malignancies, and is a major disease that seriously threatens the lives and health of children [1]. From 2016 to 2018, the average annual incidence of leukemia among children aged 0-14 in China was 42.9 per million and the number of leukemia cases every year was about 8,000 [2].…”
Section: Introductionmentioning
confidence: 99%